Pengoptimalan Ruang Pasar Rakyat Kota Batu (Selasar, 2022)
Batu City, where most of its residents are farmers, vegetables and fruits are abundant but have not been managed optimally. The market in Kota Batu is still not feasible because the spatial arrangement has not been maximized and the supporting facilities are inadequate, with this study aimed at developing market design concepts namely "Market Space Optimization". The analytical method used in this study includes qualitative descriptive analysis, physical and non-physical analysis. And hopefully the concept of "Market Space Optimization" is expected to overcome all the previous mistakes. So that the Pasar Rakyat Kota Batu can be a place of trade for residents of Batu City and to increase the economic value of Batu City.